Application of PLGA/FGF-2 coaxial microfibers in spinal cord tissue engineering: an in vitro and in vivo investigation. (5th October 2018) - Reis, Karina P; Sperling, Laura E; Teixeira, Cristian; Paim, Ágata; Alcântara, Bruno; Vizcay-Barrena, Gema; Fleck, Roland A; Pranke, Patricia
Aim: Scaffolds are a promising approach for spinal cord injury (SCI) treatment. FGF-2 is involved in tissue repair but is easily degradable and presents collateral effects in systemic administration. In order to address the stability issue and avoid the systemic effects, FGF-2 was encapsulated into core–shell microfibers by coaxial electrospinning and its in vitro and in vivo potential were studied. Materials & methods: The fibers were characterized by physicochemical and biological parameters. The scaffolds were implanted in a hemisection SCI rat model. Locomotor test was performed weekly for 6 weeks. After this time, histological analyses were performed and expression of nestin and GFAP was quantified by flow cytometry. Results: Electrospinning resulted in uniform microfibers with a core–shell structure, with a sustained liberation of FGF-2 from the fibers. The fibers supported PC12 cells adhesion and proliferation. Implanted scaffolds into SCI promoted locomotor recovery at 28 days after injury and reduced GFAP expression.Conclusion: These results indicate the potential of these microfibers in SCI tissue engineering.